2017
DOI: 10.1159/000453580
|View full text |Cite
|
Sign up to set email alerts
|

Naringin Reverses Neurobehavioral and Biochemical Alterations in Intracerebroventricular Collagenase-Induced Intracerebral Hemorrhage in Rats

Abstract: Intracerebral hemorrhage (ICH) contributes to 10-15% of all strokes and is a high risk factor for morbidity and mortality as compared to other subtypes of stroke, that is, cerebral ischemia and subarachnoid hemorrhage. Oxidative stress (OS)-induced neuroinflammation and neuronal cell death contribute towards the hallmarks of ICH. Spared antioxidant levels, increased inflammatory cytokines and free radicals in ICH lead to neuronal death and exaggerate the hallmarks of ICH. Intracerebroventricular (ICV) collagen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 75 publications
1
17
0
Order By: Relevance
“…Danhong-a traditional Chinese medicine extracted from 2 herbs (Salviae miltiorrhiza Bunge (Danshen, China) and Carthamus tinctorius L (Honghua, China))-contains flavonoids and phenolic compounds and was reported to increase the expression of peroxiredoxin (Prx) 1 in astrocytes, thereby preventing severe brain injury following ICH in aged rats [102]. In addition, carnosine [103], COA-Cl (a novel synthesized nucleoside analog) [104], AE1-259-01 EP2 receptor agonists [105], green tea and red tea [57], protocatechuic acid (PCA) [106], nebivolol [107], 14Adiponectin (APN) [108], metformin [109], C1q/tumor necrosis factor-related protein 3 (CTRPs) [15], gastrodin [110], Naringin (NGN) [111], and Parthenolide (PN) [112] are all effective antioxidants in ICH animal models.…”
Section: Peroxisome Proliferator-activated Receptor (Ppar) γmentioning
confidence: 99%
“…Danhong-a traditional Chinese medicine extracted from 2 herbs (Salviae miltiorrhiza Bunge (Danshen, China) and Carthamus tinctorius L (Honghua, China))-contains flavonoids and phenolic compounds and was reported to increase the expression of peroxiredoxin (Prx) 1 in astrocytes, thereby preventing severe brain injury following ICH in aged rats [102]. In addition, carnosine [103], COA-Cl (a novel synthesized nucleoside analog) [104], AE1-259-01 EP2 receptor agonists [105], green tea and red tea [57], protocatechuic acid (PCA) [106], nebivolol [107], 14Adiponectin (APN) [108], metformin [109], C1q/tumor necrosis factor-related protein 3 (CTRPs) [15], gastrodin [110], Naringin (NGN) [111], and Parthenolide (PN) [112] are all effective antioxidants in ICH animal models.…”
Section: Peroxisome Proliferator-activated Receptor (Ppar) γmentioning
confidence: 99%
“…Chinese herbal medicines are extensively reported to kill tumor cells, as well as to not be susceptible to drug resistance and to have few adverse effects ( 8 ). Naringin is a bioflavonoid and polyphenolic compound that is located in grapefruit ( 9 ). Previous studies have indicated that naringin has a number of pharmacological activities, including anti-inflammation, anti-oxidative stress, myocardial protection, and the regulation of glucose and lipid metabolism ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high BP in the cranium, herniation in the brain occurs, which is characteristic of ischemic stroke [3], resulting in neurological deficits or loss of neurological functions in the brain [26]. To evaluate this, we have tested the animals for their functional and neurological deficits by a series of tests such as spontaneous motility, forelimb suspension, Rotarod test, plane righting reflex, negative geotaxis reflex, and cliff avoidance [27].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, CH often results in dysfunction of the cerebral nervous system and people affected would be forced to be away from social functioning and depend on others for their self-care [1,2]. The primary effects of CH are an increase in intracranial pressure owing to blood leak and its related mechanical shear of harmful neurons and glial cells [3]. Erythrocyte lysis products and damaged microg-lia would complicate into secondary brain injury with oxidative stress and increased inflammation [4] triggering a series of events involving inflammatory and oxidative stress pathways accounting for the pathophysiological processes [5][6][7].…”
Section: Introductionmentioning
confidence: 99%